The impact of psychiatric comorbidity on length of stay of medical inpatients - Furlanetto, Letícia M; da Silva, Roberta V; Bueno, J.oão Romildo (General hospital psychiatry, 2003)
The aim of the study was to determine the impact of psychiatric comorbidity (PC) on length of hospital stay (LOS) of medical inpatients. A prospective cohort study was conducted. A series of 317 medical inpatients consecutively admitted to the general medical wards of a University Hospital composed the sample, after excluding those who refused or who could not be evaluated due to their physical illnesses or treatments ( n=78). Data on demographic and medical variables were collected. A psychiatrist categorized subjects into two cohorts (with and without PC), according to DSM-IV, using the Schedule for Affective Disorders and Schizophrenia, except in patients cognitively impaired who were diagnosed by clinical interview. Mortality and length of stay during the index hospitalization were recorded. At admission, 156 (49%) inpatients had a current psychiatric comorbidity. After controlling for confounders (age and physical severity), in the multivariate analysis of covariance, the patients with cognitive impairment had a significantly prolonged LOS (F=17.8; P<.01) compared with those without cognitive impairment. No difference existed in LOS for the patients with depressive disorders (F=0.36; P=.55), Anxiety disorders (F=1.48; P=.22) or Substance related disorders (F=1.05; P=.30). These results suggest an independent effect of cognitive impairment increasing LOS of medical inpatients.